The Influence Of Product Quality, Entrepreneurship Orientation, And Product Innovation On Competitive Advantage In Ams Aq-uascape Sidoarjo - Rezki Aulia Pramudita; Bella Sinta Martian Ardi (IQTISHADequity jurnal MANAJEMEN, 2022)
This study aims to prove and analyze the effect of product quality, entrepreneurial orientation, and product innovation on the competitive advantage at AMS Aquascape Sidoarjo. They are using quantitative research methods with multiple linear regression analysis techniques. The number of samples is 100 questionnaires using the Accidental Sampling method, a coincidental sampling technique. The results of the study partially show that product quality and entrepreneurial orientation have a positive and insignificant effect on competitive advantage. While product innovation has a positive and significant impact on competitive advantage